'Architecture is forever unfinished'. (April 2021) - Escobedo, Frida
In this interview, the celebrated Mexican architect Frida Escobedo explains the intricacies of her design practice and her longstanding interests in Minimalism, Mexican Modernism, and the socio-political concerns facing architecture. The interview provides an insightful mid-career look at one of the most creative and compelling architects working in the world today. Escobedo and Gardner engage in a lively discussion that ranges from design theory to feminism in contemporary architecture. The interview was conducted at Harvard University on 12 December 2019.